2014
DOI: 10.1007/s10681-014-1302-2
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of a gene encoding LRR protein and its validation as candidate gall midge resistance gene, Gm4, in rice

Abstract: The Asian rice gall midge, Orseolia oryzae, is an important pest of rice. Gm4, a major rice gall midge resistance gene in the indica rice variety Abhaya has been fine mapped within 0.3 Mb region with the flanking markers RM22551 and RM22562. Among the 70 putative candidate genes identified in the reference Nipponbare rice genome in this region, two genes coding for leucine rich repeat (LRR) proteins were shortlisted for further analysis.Polymorphisms was observed between the parents improved samba masuri (ISM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…However, in the present study this gene was not induced in rice line RPNF05. The target gene Gm4 in this line displayed 2 to 4 fold upward induction in stem tissue at 24 hai as earlier characterized (Divya et al 2015 ). This induction was not affected by simultaneous infection of the plant with BB pathogen.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…However, in the present study this gene was not induced in rice line RPNF05. The target gene Gm4 in this line displayed 2 to 4 fold upward induction in stem tissue at 24 hai as earlier characterized (Divya et al 2015 ). This induction was not affected by simultaneous infection of the plant with BB pathogen.…”
Section: Discussionsupporting
confidence: 78%
“…Against the Asian rice gall midge 11 genes have been reported including one recessive; of which eight have been mapped and three genes cloned (Bentur et al 2016 ). Among these Gm1, gm3 , Gm4 and Gm8 are effective against most of the seven prevailing biotypes in India (Bentur et al 2011 ) and linked markers have been reported (Sundaram 2007 ; Dutta et al 2014 ; Sama et al 2014 ; Divya et al 2015 ). There have been several successful attempts to introgress and pyramid these genes through marker assisted selection in elite genetic backgrounds.…”
Section: Introductionmentioning
confidence: 99%
“…gm3 was mapped to a 560 kb region in RP2068-18-3-5 and a gene encoding an NB-ARC protein was tentatively linked to gall midge resistance (Sama et al 2014). GM4 from Abhaya was finely mapped to a 300 kb region; this region includes a candidate gene encoding a leucine-rich repeat (LRR) protein (Divya et al 2015). GM8 from the indica rice variety Aganni was mapped to a 430 kb region containing a gene encoding a proline-rich protein (Divya et al 2018).…”
Section: Insect Resistance Gene Mappingmentioning
confidence: 99%
“…A series of near-isogenic lines (NILs) with a single BPH resistance gene/QTL, including BPH3, bph4, BPH6, BPH9, BPH10, BPH14, BPH15, BPH17, BPH18, BPH20, BPH21, BPH24, BPH26, BPH32, qBPH3, and qBPH4, were developed in the background of the susceptible cultivar 9311 and IR24, respectively (Qiu et al 2010;Xiao et al 2016;. Furthermore, the NILs with a single GM (GM4, GM11), WBPH (Ovc, qOVA-1-3, qOVA-4, qOVA-5-1, and qOVA-5-2), and GRH (GRH1, GRH2, GRH4, GRH5, GRH6, and qGRH4) resistance genes were also developed (Yamasaki et al 2003;Fujita et al 2010b;Himabindu et al 2010;Divya et al 2015). Unfortunately, such plants bearing single resistance genes lost their efficacy in just a few years as the insect populations rapidly adapted or evolved to overcome the resistance (Jena and Kim 2010).…”
Section: Marker-assisted Selectionmentioning
confidence: 99%
“…A number of loci conferring resistance to aphids, planthoppers and gall midges have been genetically identified and mapped (Smith and Clement 2012;Yasala et al 2012;Fujita et al 2013;Kamphuis et al 2013;Harris et al 2015). While only a small number of these resistance (R) genes have been cloned and functionally tested for their roles in resistance, several R loci span genes with NLR domains (Zhang 2007;Kamphuis et al 2013;Sama et al 2014;Divya et al 2015). To date, R genes to phloem-feeding hemipteran insects have been isolated from rice, tomato and melon.…”
Section: Intracellular-localized Immune Receptorsmentioning
confidence: 99%